Preparation of cation exchanger from lemon and sorption of divalent heavy metals - Arslanoğlu, Hasan; Altundoğan, Hamdi Soner; Tümen, Fikret (My University, 2008)
A cation exchanging material was developed from lemon by modifying the pectic–cellulosic substances in the lemon peel by lemon juice having citric acid. For this purpose, chopped lemon removed from seeds and yellow skin was heated in two stages, firstly at 50 °C for 24 h and subsequently at 120 °C for 2 h. The material obtained was ground, repeatedly washed with water and dried. Lemon peel and lemon resin obtained were characterized through physicochemical analyses and FTIR spectroscopy. Heavy metal binding performance of this material was determined by removal tests conducted by using 10 mM solutions of divalent metals. Experimental results show that the resin prepared from lemon is effective especially for Pb and Cu removals. For a lemon resin dosage of 10 g l?1, sorption affinity of divalent metal ions is found to be in an order of Pb > Cu > Ni > Fe > Cd > Zn > Co > Mn. Typically, sorption capacities are about 0.87 and 0.43 mmol g?1 for Pb and Mn, respectively.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Lemon peel; Lemon juice; Cation exchanger; Cross-link; Heavy metal removal